Network-Based Fractional-Order Control Algorithms for Vehicle Platooning - Omar Hanif; Patrick Gruber; Aldo Sorniotti; Umberto Montanaro (IEEE Access)
Fractional-order controllers have been shown to be an effective solution for improving the tracking performance of closed-loop control systems in various engineering applications. However, the use of fractional-order solutions has only been marginally investigated for controlling platoons of vehicles. Hence, this paper proposes three novel distributed fractional-order controllers, in which the vehicle platooning control problem of a set of homogeneous followers, characterised by either second- or third-order systems, is reformulated as a consensus control problem. The resulting closed-loop systems are analysed using the root locus approach to determine the region of control gains that ensures asymptotic closed-loop stability. Furthermore, the residual spacing errors to constant leader accelerations and disturbances are computed by analysing the error dynamics in the Laplace domain. The genetic algorithm is then employed for parameter optimisation within the stable region for different scenarios, and numerical analysis supports the theoretical findings and shows reduced tracking error when the fractional-order solutions replace their integer-order counterparts.